Dynamic Behaviour of a Zinc Roaster Furnace - Saxén, Björn; Nyberg, Jens; Härkönen, Jussi; Toivonen, Hannu (IFAC Proceedings Volumes, 2004)
Dynamic models were identified for input-output relations in a fluidised bed furnace where zinc concentrate is oxidised. Data for model development were produced by step-change experiments in six manipulated variables. Four output variables were studied; two temperatures, the pressure loss in the bed and the off-gas oxygen content. ARMAX model structures could well describe the relations studied, although some of the disturbances remained unmodelled. A multivariable control application for production maximisation will be the subject of further work.